Comparing different accounts of inversion errors in children's non-subject wh-questions: ‘What experimental data can tell us?’ - AMBRIDGE, BEN; ROWLAND, CAROLINE F.; THEAKSTON, ANNA L.; TOMASELLO, MICHAEL (Journal of child language, 2006)
This study investigated different accounts of children's acquisition of non-subject wh-questions. Questions using each of 4 wh-words (what, who, how and why), and 3 auxiliaries (BE, DO and CAN) in 3sg and 3pl form were elicited from 28 children aged 3;6–4;6. Rates of non-inversion error (Who she is hitting?) were found not to differ by wh-word, auxiliary or number alone, but by lexical auxiliary subtype and by wh-word+lexical auxiliary combination. This finding counts against simple rule-based accounts of question acquisition that include no role for the lexical subtype of the auxiliary, and suggests that children may initially acquire wh-word+lexical auxiliary combinations from the input. For DO questions, auxiliary-doubling errors (What does she does like?) were also observed, although previous research has found that such errors are virtually non-existent for positive questions. Possible reasons for this discrepancy are discussed.